A Study of the Iconography in the Narrations of the Wives of the Holy Prophet in Terms of Women, Children, Orphans and Widows - Mahak Bano; Dr. Aqeel Ahmad (Journal of Religion and Society, 2025)
The life of the Prophet (peace and blessings of Allah be upon him) was a practical example of mercy, compassion, wisdom, and good behavior. The wives of the Prophet (peace be upon him) not only held a high position among the Ummah of the Believers, but they were also the closest witnesses to the private life of the Prophet (peace be upon him). Through them, we come to know those aspects of the Prophet (peace be upon him) that transcend the public and social sphere and reflect purely domestic, emotional and social attitudes. Especially when it comes to women, children, orphans and widows, their narrations reveal the high moral character of the Prophet (peace be upon him) as an exemplary leader. If we study women in the Prophet Muhammad’s (peace be upon him) biography, we find that women enjoy countless honors, as women are the beloved of the Prophet in this world. This is why he emphasized the rights and affairs of women. If we look at the beloved things of the Prophet (peace be upon him) in this world, it becomes clear that women are also among the things he loved. The beautiful moments the Prophet (peace be upon him) spent with children in the form of sketches are part of Islamic history, as is the Prophet's service to Hazrat Anas (may Allah be pleased with him) and his lifelong refusal to even say "Oh!" to him, a life-long example. Keyword: Prophetic Qualities, Rights, Children, Women, Orphans, Widows, Matters